Effects of Dietary Strawberry Supplementation on Antioxidant Biomarkers in Obese Adults with Above Optimal Serum Lipids. (27th June 2016) - Basu, Arpita; Morris, Stacy; Nguyen, Angel; Betts, Nancy M.; Fu, Dongxu; Lyons, Timothy J.
Abstract : Berries have shown several cardiovascular health benefits and have been associated with antioxidant functions in experimental models. Clinical studies are limited. We examined the antioxidant effects of freeze-dried strawberries (FDS) in adults [n = 60 ; age:49 ± 10 years; BMI:36 ± 5  kg/m 2 (mean ± SD)] with abdominal adiposity and elevated serum lipids. Participants were randomized to one of the following arms: low dose strawberry (25 g/day FDS), low dose control beverage (LD-C), high dose strawberry (50 g/d FDS), and high dose control beverage (HD-C) for 12 weeks. Control beverages were matched for calories and total fiber. Plasma antioxidant capacity, trace elements (copper, iron, selenium, and zinc), whole blood glutathione (GSH), and enzyme activity (catalase, glutathione peroxidase, and glutathione reductase) were examined at screening (0 week) and after 12 weeks' intervention. At 12 weeks, plasma antioxidant capacity and glutathione levels were higher in the strawberry versus control groups (low and high dose FDS: 45% and 42% for plasma antioxidant capacity and 28% and 36% for glutathione, resp.); glutathione was higher in the high versus low dose strawberry group (allp < 0.05 ). Serum catalase activity was higher in the low dose strawberry (43%) versus control group (p < 0.01 ). No differences were noted in plasma trace elements and glutathione enzyme activity. Dietary strawberries may selectively increase plasma antioxidant biomarkers in obese adults with elevated lipids.